A Praça Sete Jovens e a expansão do poder punitivo - Aguiar, Claudia Cristina Trigo de (2017)
This research seeks to problematize the productions of truth concerning the crimes committed against the lives of young people. It focuses at the discursive web on the means to make public a slaughter that took place on April 16, 2014, in the Sete Jovens Square, in Brasilândia, São Paulo. The name of the Square is a tribute to seven young people who were the victims of another massacre in 2007, in the same region. The research was based on Foucault's discussion of regimes of truth and the perspective of oral history, which privileges the issue of memory as a process of meaning creation. We conducted interviews and ethnographic experiments in the region, especially around the Square. The Square was built as the result of an ancient struggle by the region's residents in order to guarantee a leisure place. However, the disputes over its occupation show the historically constructed intersection between dangerousness, race and poverty, as well as the expansion of controls on the poor population and their circulation in public spaces, through projects that articulate "security and citizenship" and control in open air. The preferred targets of this control are children and young people, especially the black youth. Making the massacre public is a memory production job confronting what Foucault called state racism that separates those who must live from those who must die